2015
DOI: 10.1063/1.4921809
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and compositional-structural properties of ion-beam sputter deposited Er-doped TiO2−xNx films: Their potential as a temperature sensor

Abstract: Er-doped TiO2−xNx films were grown by Ar+ ion-beam sputtering a Ti + Er target under different N2 + O2 high-purity atmospheres. The compositional-structural properties of the samples were investigated after thermal annealing the films up to 1000 °C under a flow of oxygen. Sample characterization included x-ray photoelectron spectroscopy, grazing incidence x-ray diffraction, Raman scattering, and photoluminescence experiments. According to the experimental data, both composition and atomic structure of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…If one takes into account that nitrogen is present in about one third of the films (30 nm instead of 90 nm), then carrier concentration would be in such region and in average about 210 20 cm -3 (it should be higher close to the surface). Such corrected carrier concentration starts to be similar to values obtained in the literature as 310 20 cm -3 for Ta:TiO 2 and 10 21 cm -3 for Nb:TiO 2 [35,34] concentration values, such as 1.510 20 cm -3 for FTO, or about 20 21 cm -3 for ITO and AZO [37, 38,39]. Similarly, sheet resistance (or resistivity) in the region would be 3 fold smaller than in the thin film average.…”
Section: Electrical Characterizationsupporting
confidence: 84%
See 1 more Smart Citation
“…If one takes into account that nitrogen is present in about one third of the films (30 nm instead of 90 nm), then carrier concentration would be in such region and in average about 210 20 cm -3 (it should be higher close to the surface). Such corrected carrier concentration starts to be similar to values obtained in the literature as 310 20 cm -3 for Ta:TiO 2 and 10 21 cm -3 for Nb:TiO 2 [35,34] concentration values, such as 1.510 20 cm -3 for FTO, or about 20 21 cm -3 for ITO and AZO [37, 38,39]. Similarly, sheet resistance (or resistivity) in the region would be 3 fold smaller than in the thin film average.…”
Section: Electrical Characterizationsupporting
confidence: 84%
“…Main features observed by XPS are expected for TiO 2 and for TiN. In situ XPS on TiO 2 samples grown at 400 and 500°C (not shown) are similar to those in ref [14] and [21], typical for Anatase film close to stoichiometry. It must be noted that absolute binding energies are not accurately known due to some degree of uncontrolled spectral shift that is attributed to sample charging.…”
Section: Composition and Structural Characterizationsupporting
confidence: 79%
“…The very broad, weak peak located between 800 and 850 nm in Er:TiO 2 /MWCNT (centered at ∼768 nm for neat TiO 2 ) has been associated with interstitial defects in the TiO 2 nanocrystals. , Other authors have reported that although this PL originates because of defects in the TiO 2 matrix, Er 3+ ions (or atoms) also increase the defect density. However, because they show ( 4 I 9/2 → 4 I 15/2 ) transitions near ∼800 nm, they are able to introduce electronic states in the bandgap of TiO 2 , thus the red-NIR PL signal observed . An important observation is the obviously diminished luminescence intensity between neat TiO 2 and the Er 3+ and MWCNT modified nanocomposites, suggesting a decrease in the electron–hole recombination rate.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have evaluated the modification of TiO 2 with rare earth metal ions and nonmetals and it has been found that the visible-light photoactivity was dependent on the anatase–rutile fractions present in titania; electron–hole recombination and interfacial charge transfer rates. Erbium ([Xe] 4f 11 ) is one of the rare earth elements (electron configuration: ([Xe] 4f n ‑1 5d 0–1 6s)) that have been used as dopants in TiO 2 and other semiconductor oxides for a range of applications such as up-conversion layers for solar cells, photocatalyst-mediated pollution remediation and temperature-sensing because the electrons in the partially occupied 4f subshell absorb infrared, visible, and ultraviolet radiation to attain numerous possible excited state configurations and can impart unique photoluminescence properties to their hosts , …”
Section: Introductionmentioning
confidence: 99%
“…The present thulium-doped TiO 2 sample was deposited onto a crystalline silicon substrate by sputtering a high purity Titanium + Thulium solid target (properly adjusted according to the Ti and Tm relative areas and sputtering yields 46 ) to generate a Tm concentration around 0.5 at.% 18 . During deposition, the Ti + Tm target was bombarded by a beam of Ar + ions (1.5 keV and nominal current ~13 mA/cm 2 ) that was generated by a Kaufman cell.…”
Section: Methodsmentioning
confidence: 99%